1992
DOI: 10.1203/00006450-199211000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxidative Metabolism during Hypothermia and Circulatory Arrest in Newborn Dogs

Abstract: ABSTRACT. To ascertain the alterations in cerebral oxiHypothermic circulatory arrest has become an established dative and energy metabolism that occur during hypother-procedure for the operative correction of congenital heart anommic circulatory arrest, nitrous oxide-anesthetized, para-alies in infants and children (1). Despite the prevalence of its use lyzed, and artificially ventilated newborn dogs were surface in clinical practice, little basic research has been conducted to cooled to 18-20°C, after which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, the normally low-energy requirement of the newborn brain may mask fluctuations in the oxidation-reduction level of the enzyme and effect the reliability of ACytaa3 as a marker of actual changes in oxidation of the enzyme Cytaa3 [35], In this respect, however, it is important to mention the results of a recent study in hypoxic newborn pigs which showed that reduction of Cytaa3, measured by NIRS, predicted indeed cerebral energy loss in these animals [36], Although the value of ACytaa3 as a marker of brain cell oxygenation remains uncertain so far, our results suggest a role for ACytaa3 as a relative measure for cerebral oxi dation. Yager et al [7] showed in newborn dogs major perturbations in the energy status of the brain early after the start of hypother mic circulatory arrest: ATP was preserved only during the first 10 min after the start of circulatory arrest in the parietal cortex, sug gesting alterations in oxidative and energy metabolism thereafter. This is in concert with the decrease in Cytaa3 in all 3 patients shortly after the beginning of the circulatory arrest (mean decrease 4.20 prnol/1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the normally low-energy requirement of the newborn brain may mask fluctuations in the oxidation-reduction level of the enzyme and effect the reliability of ACytaa3 as a marker of actual changes in oxidation of the enzyme Cytaa3 [35], In this respect, however, it is important to mention the results of a recent study in hypoxic newborn pigs which showed that reduction of Cytaa3, measured by NIRS, predicted indeed cerebral energy loss in these animals [36], Although the value of ACytaa3 as a marker of brain cell oxygenation remains uncertain so far, our results suggest a role for ACytaa3 as a relative measure for cerebral oxi dation. Yager et al [7] showed in newborn dogs major perturbations in the energy status of the brain early after the start of hypother mic circulatory arrest: ATP was preserved only during the first 10 min after the start of circulatory arrest in the parietal cortex, sug gesting alterations in oxidative and energy metabolism thereafter. This is in concert with the decrease in Cytaa3 in all 3 patients shortly after the beginning of the circulatory arrest (mean decrease 4.20 prnol/1).…”
Section: Discussionmentioning
confidence: 99%
“…The drop of Cytaa3 was small in this patient, but this was probably related to the short duration of the circulatory arrest. Experimen tal studies in newborn dogs showed indeed that especially extended periods of circulatory arrest (> 1 h) were related with cerebral (sub)-cortical and hippocampal damage [6,7], whereas the seizure incidence in 171 neonates and young infants undergoing an arterial switch procedure, was significantly higher in those patients who had circulatory arrest as compared to those without circulatory arrest [27], Recently, several investigators advo cated low-flow cardiopulmonary bypass as an alternative for circulatory arrest to prevent perturbations in cerebral metabolism during deep hypothermic CPB in infants undergoing open-heart surgery [27,30,31], Cytaa3 is the terminal enzyme of the mito chondrial electron transport chain. If oxygen delivery to the brain cell drops to low levels, this intracerebral enzyme becomes progres sively reduced [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low cholesterol/reduced saturated fat diets have been used in pediatric and adult CESD, although this has also demonstrated low efficacy. 39 , 40…”
Section: Clinical Management Of Lal-dmentioning
confidence: 99%
“…28 The mechanisms by which cooling after hypoxia–ischaemia prevent cell death are less clear. Hypothermia prevents the delayed decline in phosphocreatine and adenosine triphosphate, as well as the simultaneous increase in cerebral lactate concentration, seen 8–12 hours after hypoxia–ischemia in newborn piglets 22…”
Section: How Cooling Workmentioning
confidence: 99%